Assembling the salon: Learning from alternative forms of body work in dementia care. Issue 8 (22nd August 2016) - Ward, Richard; Campbell, Sarah; Keady, John
Abstract: This article explores the labour and experiences of a hitherto entirely overlooked section of the dementia care workforce: care‐based hairdressers. Reporting on findings from the ESRC‐funded 'Hair and Care' project, the analysis and discussion focus upon the 'doing of hair' in the context of dementia care. The authors challenge existing assumptions and approaches to the management of appearance in dementia care, arguing for greater recognition of the subjective and culturally meaningful qualities of a visit to the salon. The article draws upon a wider debate on body work as a framework for the discussion, and considers the employment and working conditions of this largely hidden group of workers in the care system. The article offers an account of the praxis of care‐based hairdressing, with particular attention paid to narrative, intercorporeal and place‐making practices in the salon, showing how a particular approach to the body shapes the labour, relationships and activities that unfold within it. The authors argue that as an alternative form of body work much can be learned from hairdressing that can inform and enhance the provision of dementia care.